2000
DOI: 10.1002/1098-1004(200007)16:1<88::aid-humu16>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of BRCA1 and BRCA2 genes in Chinese ovarian cancer identifies 6 novel germline mutations

Abstract: Communicated by Daniel F. SchorderetGermline mutations in the BRCA1 and BRCA2 genes predispose women to breast and ovarian cancer. An incidence of 5% and 3.3% respectively has been reported of BRCA1 and BRCA2 mutations in women with ovarian cancer unselected for family history. The contribution of BRCA1 and BRCA2 mutations to ovarian cancer in Chinese women is unknown. A total of 60 samples of ovarian cancer diagnosed in Chinese unselected for age or family history were analyzed for BRCA mutations using the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 13 publications
1
29
3
Order By: Relevance
“…These include 1529del4; reported in British and United States women (21), 6633del5, which was observed previously in Austrian, Japanese, and Italian women (26 -29,) and is also noted in the Breast Cancer Information Core, an international and voluntary, web-based databank of BRCA1 and BRCA2 mutations reported by Ͼ20 participating groups (30). 6 Although not highly quantitative, the Breast Cancer Information Core provides a valuable resource for tracking the occurrence of mutations throughout both the BRCA1 and BRCA2 genes. Also observed was a 5301insA change in BRCA2, reported several times in European women (29,31,32) and in women of Near and Middle Eastern descent in the Breast Cancer Information Core.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These include 1529del4; reported in British and United States women (21), 6633del5, which was observed previously in Austrian, Japanese, and Italian women (26 -29,) and is also noted in the Breast Cancer Information Core, an international and voluntary, web-based databank of BRCA1 and BRCA2 mutations reported by Ͼ20 participating groups (30). 6 Although not highly quantitative, the Breast Cancer Information Core provides a valuable resource for tracking the occurrence of mutations throughout both the BRCA1 and BRCA2 genes. Also observed was a 5301insA change in BRCA2, reported several times in European women (29,31,32) and in women of Near and Middle Eastern descent in the Breast Cancer Information Core.…”
Section: Discussionmentioning
confidence: 69%
“…An analysis of 60 ovarian cases from Hong Kong, unselected for family history, revealed that 11.3% and 2.1%, carried germ-line mutations in BRCA1 and BRCA2, respectively (6). A subsequent analysis of 214 consecutive ovarian cases, also from Hong Kong, suggested a founder effect associated with the 1081delG BRCA1 mutation in women of Southern Chinese descent (7).…”
Section: Introductionmentioning
confidence: 99%
“…Haplotype analysis of the patients with recurrent mutation showed that only in the two cases with 1081delG in BRCA1, shared haplotype was seen for all four markers detected. The mutations were identified in DNA extracted from representative tissue blocks and were confirmed to harbor in the germline on further PCR and DNA sequencing of non-tumor tissue [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime risk of developing ovarian cancer in BRCA1 and BRCA2 carriers is 28-44% [1,2,6,7]. Estimates of the frequency of BRCA1 and BRCA2 germline mutations in ovarian cancer patients have ranged between 2-12% and 2-6% for BRCA1 and BRCA2 mutations, respectively [2,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%